2014
DOI: 10.1007/s12262-014-1078-6
|View full text |Cite
|
Sign up to set email alerts
|

Living Donor Liver Transplantation Outcomes for Hepatocellular Carcinoma Beyond Milan or UCSF Criteria

Abstract: Liver transplantation (LT) is the most effective treatment for hepatocellular carcinoma (HCC) that arises from cirrhosis. The Milan and the University of California, San Francisco (UCSF) selection criteria have resulted in major improvements in patient survival. We assessed our outcomes for patients with HCC that were beyond the Milan and UCSF criteria after living donor liver transplantation. We reviewed the data for 109 patients with cirrhosis and HCC who underwent living donor right lobe liver transplantati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
0
5
0
1
Order By: Relevance
“…Microvascular invasion and tumor differentiation independently predicted HCC recurrence and their absence or presence stratified patients beyond the up-to-seven criteria in subgroups with lower (recurrence rate =24%) and higher (recurrence rate =45%) risk (33). Numerous more recent studies have confirmed that poor differentiation and microvascular invasion are associated with recurrence in patients within and beyond various transplant criteria (18,(34)(35)(36)(37)(38). Conversely, the absence of these risk factors may justify LT also in patients with large HCC as shown by the Toronto experience.…”
Section: Futility Rule #3: Presence Of Microvascular Invasion or Poormentioning
confidence: 99%
“…Microvascular invasion and tumor differentiation independently predicted HCC recurrence and their absence or presence stratified patients beyond the up-to-seven criteria in subgroups with lower (recurrence rate =24%) and higher (recurrence rate =45%) risk (33). Numerous more recent studies have confirmed that poor differentiation and microvascular invasion are associated with recurrence in patients within and beyond various transplant criteria (18,(34)(35)(36)(37)(38). Conversely, the absence of these risk factors may justify LT also in patients with large HCC as shown by the Toronto experience.…”
Section: Futility Rule #3: Presence Of Microvascular Invasion or Poormentioning
confidence: 99%
“…Hepatosellüler karsinom, KN'nin uygun hastalar için en iyi tedavi seçeneğini sunduğu zorlu bir hastalıktır (2,4). Nüks, bu zorlu hastalığın tedavisini daha da karmaşık hale getirir ve bu nedenle, hasta seçimi kabul edilebilir sonuçlar elde edilmesi açısından çok önemlidir.…”
Section: Discussionunclassified
“…Non significant >0.05 significant <0.05* -High significant <0.001** Chi-square X 2 5.430 P-value 0.020* This table showed comparison between no mutation and mutation of factor 5 Leiden (heterozygous genotype) in relation to presence of venous thromboembolism (Group 1) or not (Group 2) with statistical significant deference between two groups as regard Factor 5 Leiden as p-value was <0.05* This table showed comparison between the normal and abnormal cholesterol level in relation to presence of venous thromboembolism (Group 1) or not( Group2).with no statistical significant deference between the two groups as regard cholesterol as p-value was <0.05* This table showed comparison between the normal and abnormal lupus anticoagulant level in relation to presence of venous thromboembolism (group 1) or not( group2).with highly statistical significant deference between two groups as regard lupus anticoagulant as p-value was <0.001** This table showed comparison between the normal and abnormal protein c level in relation to presence of venous thromboembolism (group 1) or not (group 2) with no statistical significant deference between two groups as regard protein C as p-value was <0.05* between the normal and abnormal ALT level in relation to presence of venous thromboembolism (Group 1) or not( Group2) with no statistical significant deference between two groups as regard factor 5 Leiden as p-value was <0.05*. This table showed comparison between the normal and abnormal anticardiolipin IgG level in relation to presence of venous thromboembolism (Group 1) or not( Group2) with no statistical significant deference between two groups as regard anticardiolipin IgG as p-value was <0.05*.…”
Section: Significant Levelmentioning
confidence: 99%
“…Liver transplantation is now performed at over one hundred centers in the US, as well as numerous centres in Europe and elsewhere. Oneyear patient survival was 80-85% and outcomes continue to improve, although liver transplantation remains a formidable procedure with frequent complicatio.For adult-to-adult living donor liver transplantation, we have preferred the right lobe (Segment V, VI, VII and VIII) (2) .…”
Section: Introductionmentioning
confidence: 99%